In silico prediction of the inhibitory effect of phytochemical components extracted from Knautia sarajevensis on the main protease of SARS-CoV-2 virus - Tarik Corbo; Merima Miralem; Abdurahim Kalajdzic; Naris Pojskic (Genetics & Applications, 2022)
Essential role in replication and transcription of coronavirus makes the main protease of SARS-CoV-2 a great traget for drug design. The aim of this study was to predict structural interactions of compounds isolated from the Bosnian-Herzegovinian endemic plant Knautia sarajevensis (G. Beck) Szabó against the 3CLpro of SARS-CoV-2 virus. The three-dimensional crystal structure of SARS-CoV-2 main protease was retrieved from the RCSB Protein Data Bank and the three-dimensional structures of isolated compounds were obtained from the PubChem database. Active site was predicted using PrankWeb, while the preparation of protease and compounds was performed using AutoDock Tools and OpenBabel. Molecular docking was carried out using AutoDock Vina. Structural interactions are visualised and analyzed using PyMOL, LigPlus and UCSF Chimera. Apigenin, kaempferol, myricetin and quercetin showed the highest binding affinity for SARS-CoV-2 main protease and formed significant hydrogen bonds with the given protein. Results obtained in this study are in accordance with previous studies and showed that these compounds could potentially have antiviral effects against SARS-CoV-2. These findings indicate that K. sarajevensis could be potentially utilized as an adjuvant in the treatment of coronavirus disease 2019, but further pharmacological studies are required in order to prove the potential medicinal use of the plant.